Forty‐five year trends in overweight and obesity in an indigenous arctic inuit society in transition and spatiotemporal trends. Issue 4 (2nd May 2014) - Andersen, Stig; Rex, Karsten Fleischer; Noahsen, Paneeraq; Sørensen, Hans Christian Florian; Larsen, Nicolai Hardenberg; Mulvad, Gert; Laurberg, Peter
ABSTRACT Objectives Overweight and obesity associate with increased morbidity and premature death. Westernization of societies heralds rising obesity rates. A steep increase in body mass index (BMI) and overweight in Greenland from 1963 to 1998 led us to follow‐up on height, weight, BMI, and rates of overweight among populations in Greenland and assess time trends between different stages of transition. Methods BMI was calculated from height and weight measured on Inuit and non‐Inuit aged 50 through 69 years surveyed in 1963, 1998, and 2008 in Ammassalik district in East Greenland and in 1998 and 2008 in the capital Nuuk in West Greenland. Results A total of 1, 186 were surveyed in 1963 (52 men/63 women), 1998 (309/226), and 2008 (297/239). BMI increased with time (P < 0.001; 1963/1998/2008 23.3/24.3/26.2 kg/m2). In addition, BMI increased with urbanization in Inuit men (P = 0.001; settlements/town/city, in 1998, 23.9/24.9/25.5 kg/m2; in 2008, 25.0/26.0/27.0 kg/m2) while not in Inuit women (P = 0.18). The number of overweight Inuit (BMI >27 kg/m2) increased with time in men (4.0/25.6/33.2% in 1963/1998/2008, P = 0.001) and in women (13.6/30.7/37.3%, P = 0.001). BMI was above 30 kg/m2 in 2.0/10.8/17.5% of all Inuit men in 1963/1998/2008 (P = 0.003) and in 8.3%/23.0/24.5% of all Inuit women (P = 0.02) respectively. Conclusions Overweight and obesity rates rise with time and with societal transition in Greenland. Settlements and town are catching up with the city where the rate of increase is diminishing, although there were gender differences. Am. J. Hum. Biol. 26:511–517, 2014. © 2014 Wiley Periodicals, Inc.